Entre perspectivas e desafios: atuação do pedagogo/a na classe hospitalar - CARVALHO, Aurilene de Jesus Costa (2022)
This study sought to highlight the challenges and perspectives of the / pedagogue / a performance in the hospital class. The Amin objective of this study will help to understand the role and role of the pedagogue in a hospital class. For this purpose, we used bibliographic research as a research tool in a qualitative perspective, in which a theoretical-methodological analysis was carried out based on the re-reading of the main researches that publish important data and information on pedagogical work in hospitals. In this way, the work was subsidized from the theoretical contributions of some decrees and authors Brasil (2002), Matos (2010), Mugiati (2006), Fonseca (1999, 20030) Ribeiro (2012) and among others that were of paramount importance to carry out this study The research is systematized in three essays that bring notes about the challenges and challenges of the pedagogue in hospital classes. Since the Pedagogy DCNs (BRASIL, 2006) emphasize that the course aims to train the pedagogue to work in school and non-school spaces, however, it is clear that teacher training is prioritized for the school space, however, a pedagogy hospital that constitutes itself as a very relevant teaching area, in many cases is neglected. Thus, some teaching challenges are encountered in hospital Pedagogy, such as the denied right, professional devaluation of Hospital Pedagogy; emotional processes related to the suffering and death of student patients; Lack of the physical and professional structure created, given that continuous training is not provided, promoted and instigated.